Form and Metamorphosis. Body, art and nature between Goethe, Nietzsche and Klee - Giacomelli, Alberto (Scenari, 2021)
Starting from a comparison with Ovid’s Metamorphoses, I aim to highlight firstly the specificity of Goethe’s morphology. This morphological approach focuses on the dynamics of transformation, polarity and interdependence between mineral, vegetal and animal kingdom, revealing the central role of the body within Goethian writings on nature. Then I intend to clarify the Goethian distinction between symbol, in which the meaning matches with the “body” of the image, and allegory, which is an assembly of indirect meanings and therefore a sort of “corpse-body”. After that I developed the theme of the relationship between art and the body through the concepts of “original phenomenon” and “form of life”, showing the relevance of Goethe’s and Nietzsche’s legacy in the work of Kandinsky and Klee. Finally, I interpreted Klee’s art as a practice in which metamorphosis takes shape, that is, as a generative-fantastic act in which, in the figure, the whole physiological dynamism of nature is condensed.